Thinning on the Growth of Red Jabon Trees (Anthocephallus Macrophyllus) in the Industrial Plantation Forest Area - Daud Sandalayuk; Masrukhin; Murni Djabar; Alexander Ruruh; Ernikawati (Postgraduate, University of Mataram, 2023)
This study aims to observe the growth of red jabon (Anthocephalus macrophyllus) plants at various thinning intensities. Red jabon is a native Indonesian plant species that have the potential to develop forest plantations and reforestation ex-mining land. The research measured stem diameter and plant height at each thinning intensity. The study results are expected to provide information on the potential of red jabon cultivation and become a recommendation for red jabon wood farmers to improve the quality of company and farmer income. This research is expected to contribute to the development of thinning activities in improving the quality of red jabon tree stands, as well as providing a better understanding of this plant's cultivation and potential benefits. The thinning intensity applied 6 months the growth of Red Jabon trees in the Industrial Plantation Forest Area of PT. Global Citra Lestari showed a significant effect on stem diameter increment, 40% intensity treatment has a promising potential to enhance both stem diameter and height growth.